Applying the theory of planned behavior to healthy eating intention among Malaysian adults - Sharkawi, Ismawati; Latip, Malisah; Mohamed, Zainal Abidin (Human Resource Management Academic Research Society, 2021)
Despite the rising awareness on practicing healthy eating habits, statistics show the severity of the health state of Malaysian population. This indicates that most people may not have transformed their awareness into healthier eating behaviors. In response to this discrepancy between awareness and behavior, it is crucial to develop some basis for understanding the intention towards healthy eating as intention is believed to lead to performing desired behaviors. Therefore, this study aimed to identify the significant factors influencing Malaysians’ healthy eating intention with the application of Theory of Planned Behavior (TPB). A sample of 1,719 adults participated in this study. The data were analyzed using multiple regression analysis. All exogenous constructs consisting of attitude (? = 0.570), perceived behavioral control (? = 0.244), and subjective norm (? = 0.082) have positive and significant relationship with healthy eating intention. The model explained 56.7% of the variance in healthy eating intention with attitude being the most influential predictor. The findings confirm the applicability of TPB and provide indispensable insights in understanding the factors influencing the healthy eating intention among Malaysian adults. These findings can be used further to develop effective intervention programs in promoting healthier eating behaviors among the population.